Blastocyst Transfer In An Oocyte Donation Program: How To Reduce The Multiple Pregnancy Of High Order - Portella Ruiz, Jimmy (2015)
Commonly the assisted reproduction technology was based on the transfer of cleavage-stage embryos in day 2 or 3 after oocyte retrieval. However, in the last years is common the embryo transfer in the blastocyst-stage. The aim of the present study was to evaluate the pregnancy and implantation rates when embryo transfer was carried out in cleavage-stage embryos in day 3 or in blastocyst-stage embryos in day 5 in an assisted reproduction program with oocyte donation. 1667 cycles of assisted reproduction were studied retrospectively, 594 cycles with embryo transfer of day 3 and 1073 cycles of day 5. Implantation (29,09 % vs 44,85 %), pregnancy (51,01 % vs 61,7%) and delivery (44,28 % vs 52,19 %) rates were significantly higher with the blastocyst group transfer compared to cleavage-stage embryos group. Instead, the higher-order multiple pregnancy rates were significantly lower with the blastocyst group transfer. In conclusion, the results of this study support the blastocyst transfer in f